Design and Development of Additive Manufacturing Machine - S. U. Belgamwar; Sujit G. Gaikwad; Prasad M. Kulkarni; Chinmay H. Walvekar; Pravin S. Jetithor (International Journal of Electrical Power and Machine Systems, 2023)
Rapid prototyping, commonly referred to as 3D printing or additive manufacturing (AM), is the process of creating three-dimensional objects by layer-by-layer addition of material. It is very different from subtractive and conventional forming techniques. The goal of this special issue is to gather research and advancements in additive manufacturing (AM), with an emphasis on novel manufacturing techniques and substitute products and materials for feedstock. Although metal and polymer-based materials have been thoroughly studied in additive manufacturing (AM) methods, there is growing interest in the use of composite, glass, and ceramic materials in both creative and commercial AM processes. The final qualities and performance of AM products are largely determined by the material compositions and processing techniques used to shape and finish them.
Keywords: Additive Manufacturing (AM); Feeder System; Filament; Fused Deposition Modeling (FDM); conventional forming techniques